Mendorong Pertumbuhan Gereja dengan Merevitalisasi Jemaat Menjadi Penuai - Samuel Hutabarat; Frans H.M. Silalahi (Sekolah Tinggi Teologi Kanaan Nusantara, 2025)
This article examines efforts to encourage the growth of the Church by revitalizing the congregation to become reapers in the context of Harvest Theology. In order to grow quantitatively and qualitatively, the Church must encourage the church to evangelize. Many churches struggle with problems that make them lose focus on achieving the vision and mission of the Church. To reach the stage of sending reapers, the Church should first settle internal affairs. The writing method uses a descriptive qualitative methodology with a focus on the indepth study approach and the literature study method. The result of the research is that revitalization is needed so that the Church undergoes transformation and returns to its function as a Church that reaps and makes disciples. The restored Church will move the congregation to harvest actively which produces positive growth so that it becomes a healthy and spiritually mature Church. The conclusion of the research is that Harvest Theology is an effective evangelistic method that encourages children of God to become a militant evangelist who harvest in God’s reaped fields, brings the harvest to the House of God to be discipled, and produces multiplication of souls. And in time, the disciples will be sent by the Church to harvest other unsaved souls. This process continues to roll until the growth and multiplication of the Church is achieved.AbstrakArtikel ini mengkaji upaya mendorong pertumbuhan Gereja dengan merevitalisasi jemaat untuk menjadi penuai dalam konteks Harvest Theology. Untuk dapat bertumbuh secara kuantitatif dan kualitatif, Gereja harus mendorong jemaat untuk menginjil. Banyak Gereja yang bergumul dengan berbagai masalah yang membuatnya kehilangan fokus dalam mencapai visi misi Gereja. Untuk mencapai tahap pengutusan penuai, Gereja selayaknya membenahi terlebih dahulu urusan internal. Metode penulisan menggunakan metodologi kualitatif deskriptif dengan fokus pada pendekatan indepth study dan metode studi kepustakaan. Hasil penelitian adalah revitalisasi diperlukan agar Gereja mengalami transformasi dan kembali pada fungsinya sebagai Gereja yang menuai dan memuridkan. Gereja yang telah direstorasi akan menggerakkan jemaat untuk menuai secara aktif yang menghasilkan pertumbuhan yang positif sehingga menjadi Gereja sehat dan dewasa secara rohani. Kesimpulan hasil penelitian adalah Harvest Theology merupakan metode penginjilan efektif yang mendorong setiap anak Tuhan untuk menjadi penginjil militan yang menuai ladang menguning, membawa hasil tuaian ke Rumah Tuhan untuk dimuridkan, dan menghasilkan multiplikasi jiwa. Dan pada waktunya, jiwa-jiwa yang telah dimuridkan akan diutus Gereja untuk menuai jiwa-jiwa lain yang belum diselamatkan. Hal ini menjadi suatu proses yang berjalan secara berkesinambungan hingga tercapai pertumbuhan dan multiplikasi Gereja.